2007
DOI: 10.1016/j.pain.2007.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic low back pain on older adults: A comparative study of patients and controls

Abstract: Chronic low back pain (CLBP) is one of the most common, poorly understood, and potentially disabling chronic pain conditions from which older adults suffer. Many older adults remain quite functional despite CLBP, and because age-related comorbidities often exist independently of pain (e.g., medical illnesses, sleep disturbance, mobility difficulty), the unique impact of CLBP is unknown. We conducted this research to identify the multidimensional factors that distinguish independent community dwelling older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
181
2
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(204 citation statements)
references
References 57 publications
(51 reference statements)
7
181
2
14
Order By: Relevance
“…None or weak relationships between sociodemographic characteristics and LBP-related disability were reported by other authors [43]. However, our findings and those from some other studies [36] suggest that older individuals might require more attention as they may be at a greater risk for developing subjective feelings of being disabled. On the other hand, higher educational status might be a protective factor diminishing the sense of LBPrelated disability.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…None or weak relationships between sociodemographic characteristics and LBP-related disability were reported by other authors [43]. However, our findings and those from some other studies [36] suggest that older individuals might require more attention as they may be at a greater risk for developing subjective feelings of being disabled. On the other hand, higher educational status might be a protective factor diminishing the sense of LBPrelated disability.…”
Section: Discussioncontrasting
confidence: 71%
“…Typically, the most evident consequences of the pain are limitations in mobility [15]. Many authors emphasize, however, that the effects of this disease cannot be confined only to motor dysfunctions since LBP exerts a profound negative impact also on the patients' psychological wellbeing [36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that persistent pain may contribute to, or accelerate the development of frailty in older people through mechanisms such as impaired mobility, depression, decreased nutritional intake and the burden of co-morbidities 9,10 , and interventions to improve pain management may help prevent frailty 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic low back pain (CLBP) is more prevalent in older adults than young-to-middle aged adults, and occurrence among older adults has increased significantly over recent years [4,5]. Further, older adults with CLBP are more likely than those without pain to self-report functional limitations in activities of daily living (ADLs) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transitioning from sit-to-stand, a common core component of many performance tests, requires sufficient lumbar mobility [13]. Although previous literature has shown that the presence [7,14] and severity [14,15] of CLBP are linked to poor performance, little is known regarding the role that clinically relevant, and potentially modifiable, factors (e.g., lumbar mobility) may have in the decline of performance.…”
Section: Introductionmentioning
confidence: 99%